Electrolyte for power storage device and non-aqueous electrolytic solution

By using electrolytes formed by reacting lithium-containing composite compounds with boron fluoride or phosphate fluoride in lithium-ion secondary batteries, the problems of poor stability and poor circulation performance of existing batteries at high temperatures are solved, the high energy density and long life of the battery are achieved, and it is suitable for solid-state batteries.

JP2025063235AActive Publication Date: 2025-04-15TOMIYAMA PURE CHEM IND LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2025007768
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-15
Estimated Expiration
2038-03-23

AI Technical Summary

Technical Problem

The electrolytes of the existing nonaqueous electrolyte lithium-ion secondary batteries have poor stability at high temperatures, resulting in reduced battery capacity and poor circulation performance. The lithium compound in solid-state batteries has poor conductivity, making it difficult to widely use.

Method used

An electrolyte containing lithium-containing composite compounds, such as composite compounds composed of elements such as lithium, boron or phosphorus, is used to form a stable electrolyte system by reacting with boron fluoride or phosphate fluoride, thereby improving the conductivity of lithium ions and the cycling performance of the battery.

Benefits of technology

It has achieved the improvement of the stability and cycling performance of lithium-ion secondary batteries at high temperatures, reduced the internal resistance of the battery, improved the energy density and service life of the battery, and is suitable for the application of solid-state lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063235000001
    Figure 2025063235000001
  • Figure 2025063235000002
    Figure 2025063235000002
  • Figure 2025063235000003
    Figure 2025063235000003
Patent Text Reader

Abstract

To provide an enhanced power storage device capable of maintaining a high capacity even after charging and discharging are repeated while reducing electric resistance.SOLUTION: A power storage device comprises a positive electrode, a negative electrode, and an electrolyte between both electrodes. The electrolyte contains a lithium-containing complex compound expressed by, for example, the following formulas (1) to (3): (Li)m(A)n(UFx)y (1); (Li)m(Si)n(O)q(UFx)y (2) (in the formulas, A is O, S, P, or N. U is a boron atom or a phosphorus atom. m and n are independently 1 to 6. q is 1 to 12. x is 3 or 5. y is 1 to 6), and (Li)m(O)n(B)p(OWFq)x (3) (in the formula, W is a boron atom or a phosphorus atom. m, p, and x are independently 1 to 15. n is 0 to 15. and q is 3 or 5).SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolyte for an electricity storage device such as a lithium ion secondary battery, and a nonaqueous electrolyte solution for an electricity storage device containing the electrolyte. [Background technology]

[0002] In recent years, with the widespread use of various portable electronic devices, such as portable electronic terminals typified by mobile phones and notebook computers, secondary batteries play an important role as power sources for such devices. Examples of such secondary batteries include aqueous batteries and nonaqueous electrolyte batteries. Among these, nonaqueous electrolyte secondary batteries, which are equipped with positive and negative electrodes capable of absorbing and releasing lithium ions and the like, and a nonaqueous electrolyte, have high energy density at high voltages, are excellent in safety, and have various advantages over other secondary batteries in terms of environmental issues, etc.

[0003] Examples of non-aqueous electrolyte secondary batteries currently in practical use include lithium-ion secondary batteries, which use a composite oxide of lithium and transition metals as the positive electrode active material and a material capable of doping and dedoping lithium as the negative electrode active material. Carbon materials are examples of negative electrode active materials with excellent cycle characteristics for lithium-ion secondary batteries. Among carbon materials, graphite is expected to be a material that can improve the energy density per unit volume.

[0004] In addition, in order to improve the characteristics of lithium secondary batteries, there is a demand for improvements not only in the characteristics of the negative electrode / positive electrode, but also in the characteristics of the non-aqueous electrolyte that transports lithium ions. As such non-aqueous electrolytes, non-aqueous solutions in which lithium salts such as LiBF4, LiPF6, LiClO4, LiN(SO2CF3)2, and LiN(SO2CF2CF3)2 are dissolved in aprotic organic solvents are used (Non-Patent Document 1). Carbonates are known as representative examples of aprotic organic solvents, and the use of various carbonate compounds such as ethylene carbonate, propylene carbonate, and dimethyl carbonate has been proposed (Patent Documents 1 and 2).

[0005] On the other hand, as an electrolyte for non-aqueous electrolytic solutions, non-aqueous electrolytic solutions in which LiBF4, LiPF6, or the like is dissolved are known to have high conductivity, which indicates the transport of lithium ions, and are stable at high voltages due to the high oxidative decomposition voltages of LiBF4 and LiPF6, and contribute to bringing out the high voltage and high energy density characteristics of lithium secondary batteries. When non-aqueous electrolyte secondary batteries such as lithium secondary batteries are used as power sources, there is a demand for a longer life by reducing the electrical resistance of the non-aqueous electrolyte to increase the conductivity of lithium ions, and by suppressing the decrease in battery capacity and maintaining a high capacity even after repeated charging and discharging, that is, by improving so-called cycle characteristics.

[0006] In order to achieve this purpose, it has been proposed to modify the structure of the lithium salt, which is the electrolyte contained in the non-aqueous electrolyte, or to add a specific compound. For example, Patent Document 3 proposes adding a vinyl sulfone derivative having a specific structure to the non-aqueous electrolyte. In addition, Patent Document 4 proposes adding a lithium salt other than a bifunctional lithium salt having a specific structure, which does not have a boron atom.

[0007] Meanwhile, all-solid-state lithium batteries that are free from concerns about battery ignition due to the flammability of organic solvents in non-aqueous electrolytes have been known, and amorphous compounds in which lithium salts such as lithium sulfide are reacted with boron sulfide, phosphorus sulfide, silicon sulfide, etc., are known as lithium ion conductive solid electrolytes therein (Patent Documents 5 and 6). However, these lithium compounds generally lack solubility in non-aqueous electrolytes, making them difficult to use as electrolytes for power storage devices. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 4-184872 [Patent Document 2] Japanese Patent Application Publication No. 10-27625 [Patent Document 3] Japanese Patent Application Publication No. 11-329494 [Patent Document 4] JP 2014-22334 A [Patent Document 5] Japanese Patent Application Publication No. 11-219722 [Patent Document 6] JP 2003-68361 A Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide an electrolyte for electricity storage devices such as lithium secondary batteries that can be used in place of lithium salts, which are known electrolytes in non-aqueous electrolyte solutions of electricity storage devices, or can be used in combination with known lithium salts, and can also be used as an all-solid-state electrolyte that does not use a non-aqueous solvent and is free from the risk of fire or the like. Another object of the present invention is to provide an electricity storage device such as a non-aqueous electrolyte type or all-solid-state type lithium secondary battery using the above electrolyte, and a non-aqueous electrolyte and a solid electrolyte used therein. [Means for solving the problem]

[0010] The present inventors conducted various studies and found a novel electrolyte for an electricity storage device that can achieve the above-mentioned object. This electrolyte is soluble in a non-aqueous solvent for an electricity storage device such as a lithium ion secondary battery, so that a non-aqueous electrolyte solution with low electrical resistance can be obtained, and a lithium secondary battery with good initial characteristics and excellent cycle characteristics can be obtained. Furthermore, the electrolyte itself has excellent lithium ion conductivity, so that an all-solid-state lithium secondary battery can be obtained. Based on these findings, the present invention was completed.

[0011] The present invention relates to an electrolyte for an electricity storage device, comprising a lithium-containing complex compound represented by the following formula (1), (2), (3), (4) or (5). (Li) m (A) n (U.F.x ) y (1) (Li) m (Si) n (O) q (U.F. x ) y (2) (In the formula, A is O, S, P or N. U is a boron atom or a phosphorus atom. m and n each independently are 1 to 6. q is 1 to 12. x is 3 or 5. y is 1 to 6.) (Li) m (O) n (B) p (OWF q ) x (3) (In the formula, W is a boron atom or a phosphorus atom. m, p, and x each independently are 1 to 15. n is 0 to 15. q is 3 or 5.) (Li) m (B) p (O)n(OR) y (OWF q ) x (4) (In the formula, W is a boron atom or a phosphorus atom; n is 0 to 15; p, m, x, and y are each independently 1 to 12; and q is 3 or 5. R is a hydrogen atom, an alkyl group, an alkenyl group, an aryl group, a carbonyl group, a sulfonyl group, or a silyl group, and these groups may have a fluorine atom, an oxygen atom, or other substituents.) (Li) m (O) n (B) p (OOC-(A) z -COO) y (OWF q ) x (5) (In the formula, W is a boron atom or a phosphorus atom. A is an alkylene group, an alkenylene group or an alkynylene group having 1 to 6 carbons, a phenylene group, or an alkylene group having an oxygen atom or a sulfur atom in the main chain. m, p, x, and y each independently are 1 to 20. n is 0 to 15. z is 0 or 1. q is 3 or 5.) Effect of the Invention

[0012] The electrolyte for electricity storage devices of the present invention has solubility in organic solvents for electricity storage devices such as lithium ion secondary batteries, and therefore a nonaqueous electrolyte solution having low electrical resistance can be obtained, and an electrolyte for electricity storage devices such as lithium secondary batteries having good initial characteristics and excellent cycle characteristics can be obtained. Furthermore, since the electrolyte for electricity storage devices of the present invention itself has excellent lithium ion conductivity, an all-solid-state lithium secondary battery can be obtained. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] <Electrolytes> The present invention relates to an electrolyte for an electricity storage device, comprising a lithium-containing complex compound represented by the following formula (1), (2), (3), (4) or (5). (Li) m (A) n (U.F. x ) y (1) (Li) m (Si) n (O) q (U.F. x ) y (2) (In the formula, A, U, m, n, q, x, and y are defined as above.) (Li) m (O) n (B) p (OWF q ) x (3) (In the formula, W, m, p, x, n, and q are defined as above.) (Li) m (B) p (O)n(OR) y (OWF q ) x (4) (In the formula, W, R, n, p, m, x, y, and q are defined as above.) (Li) m (O) n (B) p (OOC-(A) z -COO) y (OWF q )x (5) (In the formula, W, A, m, p, x, y, n, z, and q are defined as above.)

[0014] In the above formula (1) and formula (2), A is preferably an oxygen atom, a sulfur atom, a phosphorus atom, or a nitrogen atom, and more preferably an oxygen atom or a sulfur atom, because it is easy to form a stable lithium salt and because of solubility in a solvent. U is preferably a boron atom, a phosphorus element, or an arsenic atom, and more preferably a boron atom or a phosphorus element, because it is easy to form a bond with an oxygen atom, a sulfur atom, or a nitrogen atom.

[0015] Among these, m and n are preferably 1 to 6, and particularly preferably 2 to 6. Among these, q is preferably 2 to 8, and particularly preferably 3 to 8, for the reason of the solubility of the electrolyte in the solvent. Among these, for the reason of solubility in the electrolyte solvent, x is preferably 3 or 5. Among these, y is preferably 1 to 6, particularly preferably 1 to 5, because it is easy to form a bond with an oxygen atom, a sulfur atom, a phosphorus atom, or a nitrogen atom.

[0016] Examples of the lithium-containing complex compound include O-(BF3Li)(Li), O-(BF3Li)2, S-(BF3Li)(Li), S-(BF3Li)2, N-(BF3Li)2(Li), N-(BF3Li)3, P-(BF3Li)2(Li), P-(BF3Li)3, SiO3(BF3Li)(Li), SiO3(BF3Li)2, O-(PF5Li)(Li), O-(PF5Li)2, S-(PF5Li)(Li), or S-(PF5Li)2. For the sake of convenience, the lithium-containing complex compound is described as above. For example, O-(BF3Li)(Li) is Li-O(-BF3 - Li + ) complexes with the structure

[0017] Of the lithium-containing complex compounds, O-(BF3Li)(Li), O-(BF3Li)2, S-(BF3Li)(Li), S-(BF3Li)2, N-(BF3Li)3, P-(BF3Li)3, SiO3(BF3Li)(Li) or SiO3(BF3Li)2 are preferred, and O-(BF3Li)(Li), O-(BF3Li)2, S-(BF3Li)(Li), S-(BF3Li)2, SiO3(BF3Li)(Li), SiO3(BF3Li)2, O-(PF5Li)(Li), O-(PF5Li)2, S-(PF5Li)(Li), or S-(PF5Li)2, N-(PF5Li)3 are particularly preferred, due to the stability of the lithium-containing complex compound and its solubility in a solvent.

[0018] The lithium-containing complex compound is obtained by reacting a lithium compound (A) represented by the following formula (6) or formula (7) with one or more boron fluoride compounds (B) selected from the group consisting of boron trifluoride and boron trifluoride complexes, or one or more phosphorus fluoride compounds (C) selected from the group consisting of phosphorus pentafluoride and phosphorus pentafluoride complexes. (Li) m (A) n (6) (Li) m (Si) n (O) q (7) In the formulae (6) and (7), A, m, n, and q are defined the same as in the formulae (1) and (2) above, and the preferred values ​​are also the same.

[0019] Examples of the lithium compound (A) represented by formula (3) include lithium oxide, lithium carbonate, lithium sulfide, lithium phosphide, lithium nitride, etc. Among these, lithium oxide, lithium carbonate, and lithium sulfide are preferred.

[0020] Examples of the lithium compound (A) represented by formula (6) include chain lithium inosilicates such as lithium silicate, lithium metasilicate, and lithium disilicate, lithium cyclosilicates having a cyclic structure, lithium phyllosilicates having a layered structure, and lithium tectosilicates having a three-dimensional structure. Among these, lithium silicate, lithium metasilicate, and lithium disilicate are preferred.

[0021] The boron fluoride compound (B) may be boron trifluoride or a boron trifluoride complex. The boron trifluoride complex is formed from the boron atom of boron trifluoride and the oxygen of an oxygen-containing compound, and is obtained by contacting boron trifluoride with an oxygen-containing compound. Examples of the oxygen-containing compound include water, methanol, ethanol, propanol, butanol, phenol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0022] Specific examples of the boron fluoride compound (B) include boron trifluoride, boron trifluoride dimethyl ether complex, boron trifluoride diethyl ether complex, boron trifluoride di-n-butyl ether complex, boron trifluoride di-tert-butyl ether complex, boron trifluoride tert-butyl methyl ether complex, boron trifluoride tetrahydrofuran complex, boron trifluoride methanol complex, boron trifluoride ethanol complex, boron trifluoride propanol complex, boron trifluoride butanol complex, boron trifluoride phenol complex, boron trifluoride ethylene carbonate complex, boron trifluoride ethyl methyl carbonate complex, boron trifluoride dimethyl carbonate complex, and boron trifluoride diethyl carbonate complex. Among these, boron trifluoride, boron trifluoride dimethyl ether complex, boron trifluoride diethyl ether complex, boron trifluoride methanol complex, boron trifluoride ethanol complex, boron trifluoride propanol complex, and the like are preferred.

[0023] The phosphorus pentafluoride compound (C) may be phosphorus pentafluoride or a phosphorus pentafluoride complex. The phosphorus pentafluoride complex is formed from phosphorus pentafluoride and oxygen of an oxygen-containing compound, and is obtained by contacting phosphorus pentafluoride with the oxygen-containing compound. Specific examples of the phosphorus pentafluoride compound (C) include phosphorus pentafluoride, phosphorus pentafluoride ethylene carbonate complex, phosphorus pentafluoride dimethyl methyl carbonate complex, phosphorus pentafluoride diethyl methyl carbonate complex, and phosphorus pentafluoride ethyl methyl carbonate complex. Among these, phosphorus pentafluoride, phosphorus pentafluoride dimethyl methyl carbonate complex, phosphorus pentafluoride diethyl methyl carbonate complex, and phosphorus pentafluoride ethyl methyl carbonate complex are preferred.

[0024] The lithium-containing complex compound can be obtained by contacting a lithium compound (A) with a boron fluoride compound (B) and / or a phosphorus fluoride compound (C) in the presence or absence of a solvent, preferably in an inert atmosphere, and reacting them at preferably 0 to 80° C., more preferably 10 to 30° C. The solvent is not limited as long as it is inert to the reaction, and examples of the solvent include water, methanol, ethanol, propanol, butanol, phenol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0025] Specifically, for example, the lithium compound (A) is gradually added to a liquid in which the boron fluoride compound (B) and / or the phosphorus fluoride compound (C) is dissolved or dispersed in a solvent such as methanol in an inert gas atmosphere such as argon, preferably at 0 to 50° C. Then, the reaction is allowed to proceed by stirring for 1 to 24 hours, preferably at 30 to 80° C. The reaction liquid is concentrated to remove the solvent, methanol, to obtain a crude lithium-containing complex compound. The resulting crude lithium-containing complex compound is washed with ether or the like, and the resulting purified product is dried under reduced pressure to obtain a high-purity lithium-containing complex compound.

[0026] On the other hand, in formulas (3), (4), and (5), a complex bond can be formed with W via oxygen bonded to some of the boron to form a stable boron-containing complex compound. A part or all of the boron in the lithium-containing boron complex compound can form a complex. Although the bonding form is not limited here, it is preferable that one or more bonds with W are formed with the eight boron atoms from the viewpoint of solubility in a solvent. In addition, a complex bond can be formed with one or more W on the same boron.

[0027] Among them, W is preferably a boron atom, a phosphorus atom, or an arsenic atom, and more preferably a boron atom or a phosphorus atom, because it is easy to form a bond with an oxygen atom. In addition, the ratio of the mole number of W to the mole number of lithium atoms in the lithium-containing boron complex compound is preferably 30 to 100. Among these, A is preferably an alkylene group having 1 to 6 carbon atoms, more preferably an alkenylene group having 2 to 6 carbon atoms, or an alkynylene group having 2 to 6 carbon atoms. Preferable examples of the alkylene group include methylene, ethylene, difluoromethylene, tetrafluoroethylene, hydroxyethylene, propylene, butylene, cyclopropylene, cyclobutylene, cyclohexylene, etc. Preferable examples of the alkylene group having an oxygen atom or a sulfur atom in the main chain are those in which an alkylene group having 1 to 4 carbon atoms is bonded to the oxygen atom or sulfur atom. Preferred examples of the alkenylene group include vinylene, propenylene, butenylene, pentenylene, etc. In particular, an alkenylene group having a double bond and 2 to 6 carbon atoms is preferred. Preferred examples of the alkynylene group include ethynylene, propynylene, butynylene, pentynylene, etc. In particular, an alkynylene group having 3 to 6 carbon atoms is preferred. Preferred examples of the phenylene group include phenylene and difluorophenylene. In formula (3), when A is an alkylene group, an alkenylene group, an alkynylene group, a phenylene group, or an alkylene group having an oxygen atom or a sulfur atom in the main chain, the hydrogen atoms of these groups may be optionally substituted with halogens, hydroxyl groups, cyano groups, nitro groups, or the like.

[0028] R is preferably an alkyl group, an alkenyl group, an aryl group, a carbonyl group, a sulfonyl group, a silyl group, a boron-containing group or a phosphorus-containing group, and particularly preferably an alkyl group, a carbonyl group, a sulfonyl group, a phenyl group, a silyl group, a boron-containing group or a phosphorus-containing group. n is preferably 0 to 15, and m, p, and y are preferably 1 to 20, particularly preferably 1 to 12. q is preferably 3 or 5. x is preferably 1 to 8, particularly preferably 2 to 8, for the reason of solubility of the electrolyte in the solvent.

[0029] Examples of the lithium-containing boron complex compound represented by the above formula (3) include BO(OBF3Li), B4O5(OBF3Li)2, LiB4O6(OBF3Li), and BO 13 (OBF3Li)4, B6O9(OBF3Li)2, B8O9(OBF3Li)2, B5O7(OBF3Li), B7O 10 (OBF3Li), BO(OBF3Li)3, LiBO(OBF3Li)2, Li2BO2(OBF3Li), B2O(OBF3Li)4, Li2B2O3(OBF3Li)2, B3O7(OBF3Li)5, B4O3(OBF3Li) 6, Li2B4O5(OBF3Li)4, Li2B2O(OBF3Li)6, Li3B2O2(OBF3Li)5, Li4B2O3(OBF3Li)4, Li5B2O4(OBF3Li)3, Li6B2O5(OBF3Li)2, Li2B 6O 7(OBF3Li)6, Li4B6O9(OBF3Li)4.

[0030] Examples of the lithium-containing boron complex compound represented by the above formula (4) include B(OC(=O)CH3)2(OBF3Li), B(OC(=O)CF3)2(OBF3Li), B2O(OCH3)2(OBF3Li)2, B2O(OCH2CH3)2(OBF3Li)2, B2O(OCF2CF3)2(OBF3Li)2, and B2O(OC(=O)CH3)2(OB F3Li)2, B2O(OC(=O)CF3)2(OBF3Li)2, LiB2O2(OC(=O)CF3)2(OBF3Li), B2O(OSO2CH3)2(OBF3Li) 2, B2OOSO2CF3)2(OBF3Li)2, LiB2O2(OSO2CF3)2(OBF3Li), and B2O(OSi(CH3)3)2(OBF3Li)2.

[0031] Examples of the lithium-containing boron complex compound represented by the above formula (5) include BO(OOC-COO)(OBF3Li), BO(OOCCH2COO)(OBF3Li), BO(OOC(CH2)2COO)(OBF3Li), BO(OOC(CF2)2COO)(OBF3Li), BO(OOC(CH2)3COO)(OBF3Li), BO(OOC(CH2C(=CH2))COO)(OBF3Li), BO(OOC(C(CH2)3)COO)(OBF3Li), BO(OOCCH2OCH2COO)(OBF3Li), BO(OOCCH2SCH2COO)(OBF3Li), BO(OOCC2H4SC2H4COO)(OBF3Li), B4O3(O OC-COO)2(OBF3Li)2, lib4O4(OOC-COO)2(OBF3Li), B4O3(OOCCH2COO)2(OBF3Li)2, B4O3 (OOCCH2SCH2COO)2(OBF3Li)2, LiB4O4(OOCCH2SCH2COO)2(OBF3Li), B4O3(OOC(CH2C(=CH 2))COO)2(OBF3Li)2, Li2B2O(OOC-COO)2(OBF3Li)2, Li2B2O(OOCCH2COO)2(OBF3Li)2, Li Examples include 2B2O(OOCCH2SCH2COO)2(OBF3Li)2, Li2B2O(OOC(CH2C(=CH2))COO)2(OBF3Li)2, and the like. The above expression of the lithium-containing boron complex compound does not indicate the bond structure of the complex, but the element ratio is described as above for convenience.

[0032] The content of the lithium-containing boron complex compound in the non-aqueous electrolyte of the present invention is preferably 0.01 to 30 mass%, more preferably 0.1 to 25 mass%, and particularly preferably 0.1 to 5 mass%. If the concentration is less than 0.01 mass%, the resistance reduction effect is reduced. On the other hand, if the concentration exceeds 30 weight%, the resistance component increases and the life performance is deteriorated, which is not preferable.

[0033] The lithium-containing boron complex compound is obtained by reacting a lithium-containing boron compound (D) represented by the following formula (8), formula (9), or formula (10) with one or more boron fluoride compounds (E) selected from the group consisting of boron trifluoride and boron trifluoride complexes, or one or more phosphorus fluoride compounds (F) selected from the group consisting of phosphorus pentafluoride and phosphorus pentafluoride complexes. (Li)m(B)p(O)n (8) (Li)m(B)p(O)n(OR)y (9) (Li) m [(-O-) n B(OOC-(A)z-COO) p ] x [B(-O-) q ] y (10) In formula (8), formula (9), and formula (10), A, R, m, n, p, q, x, y, and z are defined the same as in formula (3), formula (4), and formula (5) above, and the preferred ones are also the same.

[0034] In the lithium-containing boron compound represented by formula (8), m, p and n each independently represent 1-20. Preferred specific examples of the lithium-containing boron compound represented by formula (8) include LiBO2, Li2B4O7, and Li4B8O 17 , Li2B6O 11 , Li2B8O 11 , LiB5O8, LiB7O11 , Li3BO3, Li4B2O5, Li5B3O7, Li6B4O9, Li8B2O7, Li8B6O 13 etc.

[0035] In the lithium-containing boron compound represented by formula (9), n, m, x, and y are each independently 1 to 12, and R is a hydrogen atom, an alkyl group, an alkenyl group, an aryl group, a carbonyl group, a sulfonyl group, or a silyl group, and these groups may have a fluorine atom, an oxygen atom, or other substituents. R is preferably an alkyl group, an alkenyl group, an aryl group, a carbonyl group, a sulfonyl group, a silyl group, a boron-containing group or a phosphorus-containing group, and particularly preferably an alkyl group, a carbonyl group, a sulfonyl group, a phenyl group, a silyl group, a boron-containing group or a phosphorus-containing group.

[0036] The alkyl group is preferably a linear or cyclic alkyl group having 1 to 8 carbon atoms. Examples of the linear or cyclic alkyl group having 1 to 8 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a hexyl group, a cyclopropyl group, a cyclobutyl group, a cyclohexyl group, a hydroxyethyl group, a trifluoromethyl group, and a hexafluoroethyl group. The alkenyl group is preferably an alkenyl group containing a double bond and having 2 to 5 carbon atoms, and examples thereof include a vinyl group, a propenyl group, a butenyl group, and a heptenyl group.

[0037] Preferred examples of the aryl group include a phenyl group, a benzyl group, a tolyl group, and a xylyl group. Preferred examples of the carbonyl group include a methylcarbonyl group, an ethylcarbonyl group, a propylcarbonyl group, a butylcarbonyl group, a cyclopropylcarbonyl group, a cyclobutylcarbonyl group, a trifluoromethylcarbonyl group, and a pentafluoroethylcarbonyl group.

[0038] Preferred examples of the sulfonyl group include a methylsulfonyl group, an ethylsulfonyl group, a propylsulfonyl group, a benzylsulfonyl group, a trifluoromethylsulfonyl group, and a pentafluoroethylsulfonyl group. Preferred examples of the silyl group include a trimethylsilyl group, a triethylsilyl group, a triisopropylsilyl group, and a butyldimethylsilyl group. Preferred examples of the boron-containing group include a dimethylboryl group and a dimethoxyboryl group.

[0039] Preferred specific examples of the lithium boron compound represented by formula (9) include LiBO(OC(=O)CH3)2, LiBO(OC(=O)CF3)2, Li2B2O3(OCH3)2, Li2B2O3(OCH2CH3)2, Li2B2O3(OCF2CF3)2, Li2B2O3(OC(=O)CH3)2, Li2B2O3(OC(=O)CF3)2, Li2B2O3(OSO2CH3)2, Li2B2O3(OSO2CF3)2, Li2B2O3(OSi(CH3)3)2, etc.

[0040] In the lithium-containing boron compound represented by formula (10), A is an alkylene group, alkenylene group or alkynylene group having 1 to 6 carbon atoms, a phenylene group, or an alkylene group having an oxygen atom or a sulfur atom in the main chain. n and p each independently represent 1 or 2, q represents 0 to 3, and m, x, y, and z each independently represent 0 to 10. Among these, A is preferably an alkylene group, an alkenylene group, or an alkynylene group having preferably 1 to 6 carbon atoms, more preferably 2 to 6 carbon atoms. Preferred examples of the alkylene group include methylene, ethylene, tetrafluoroethylene, hydroxyethylene, propylene, butylene, cyclopropylene, cyclobutylene, cyclohexylene, and the like.

[0041] The alkenylene group is preferably an alkenylene group having a double bond containing 2 to 5 carbon atoms. Examples of the alkenylene group having a double bond containing 2 to 4 carbon atoms include vinylene, propenylene, butenylene, and pentenylene. Preferable examples of the phenylene group include phenylene, difluorophenylene, etc. Preferable examples of the alkylene group having an oxygen atom or a sulfur atom in the main chain are preferably those in which an alkylene group having 1 to 4 carbon atoms is bonded to an oxygen atom or a sulfur atom, and examples of the alkylene group include methylene, ethylene, tetrafluoroethylene, propylene, butylene, cyclopropylene, cyclobutylene, etc.

[0042] When A is an alkylene group, an alkenylene group, an alkynylene group, a phenylene group, or an alkylene group having an oxygen atom or a sulfur atom in the main chain, the hydrogen atoms of these groups may be optionally substituted with halogens, hydroxyl groups, cyano groups, nitro groups, or the like. In the formula (6), n and p are each independently preferably 1 or 2, and m, x, y and z are each independently preferably 0 to 10.

[0043] Specific preferred examples of the lithium boron compound include LiBO(OOC-COO), LiBO(OOCCH2COO), LiBO(OOC(CH2)2COO), LiBO(OOC(CF2)2COO), LiBO(OOC(CH2)3COO), LiBO(OOC(CH2C(=CH2))COO), LiBO(OOC(C(CH2)3)COO), LiBO(OOCCH2OCH2COO), LiBO(OOCCH2SCH2COO, LiBO( Examples include Li2B4O5(OOC-COO)2, Li2B4O5(OOCCH2COO)2, Li2B4O5(OOCCH2SCH2COO)2, Li2B4O5(OOC(CH2C(=CH2))COO)2, Li4B2O3(OOC-COO)2, Li4B2O3(OOCCH2COO)2, Li4B2O3(OOCCH2SCH2COO)2, and Li4B2O3(OOC(CH2C(=CH2))COO)2.

[0044] The lithium boron compound can be easily obtained by the same manufacturing method as lithium salts such as lithium tetraborate. For example, an aqueous solution of boric acid, a lithium compound such as lithium hydroxide or lithium carbonate, and a corresponding carboxylic acid compound can be kept at 20 to 80°C to easily obtain a precursor crystal. The obtained crystal is dehydrated under conditions of 200 to 400°C to suitably obtain the lithium boron compound.

[0045] The boron fluoride compound (E) may be boron trifluoride or a boron trifluoride complex. The boron trifluoride complex is formed from the boron atom of boron trifluoride and the oxygen of an oxygen-containing compound, and is obtained by contacting boron trifluoride with an oxygen-containing compound. Examples of the oxygen-containing compound include water, methanol, ethanol, propanol, butanol, phenol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl butyl carbonate.

[0046] The phosphorus pentafluoride compound (F) may be phosphorus pentafluoride or a phosphorus pentafluoride complex. The phosphorus pentafluoride complex is formed from phosphorus pentafluoride and oxygen of an oxygen-containing compound, and is obtained by contacting phosphorus pentafluoride with the oxygen-containing compound. Specific examples of the phosphorus pentafluoride compound (F) include phosphorus pentafluoride, phosphorus pentafluoride ethylene carbonate complex, and phosphorus pentafluoride ethyl methyl carbonate complex. Among these, phosphorus pentafluoride and phosphorus pentafluoride ethyl methyl carbonate complex are preferred.

[0047] The lithium-containing boron complex compound can be obtained by contacting the lithium-containing boron compound (D) with the boron fluoride compound (E) and / or the phosphorus fluoride compound (F) in the presence or absence of a solvent, preferably in an inert atmosphere, and reacting them at preferably 0 to 80° C., more preferably 10 to 30° C. The solvent is not limited as long as it is inert to the reaction, and examples of the solvent include water, methanol, ethanol, propanol, butanol, phenol, tetrahydrofuran, dimethyl ether, diethyl ether, dibutyl ether, ethylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl butyl carbonate.

[0048] Specifically, for example, the lithium-containing boron compound (D) is gradually added to a liquid in which the boron fluoride compound (E) and / or the phosphorus fluoride compound (F) is dissolved or dispersed in a solvent such as methanol in an inert gas atmosphere such as argon, preferably at 0 to 50° C. Then, the reaction is allowed to proceed by stirring for 1 to 24 hours, preferably at 30 to 80° C. The reaction liquid is concentrated to remove the solvent, methanol, to obtain a crude lithium-containing boron complex compound. The resulting crude lithium-containing boron complex compound is washed with ether or the like, and the resulting purified product is dried under reduced pressure to obtain a high-purity lithium-containing boron complex compound.

[0049] <Non-aqueous solvent> When the electrolyte of the present invention is used as a non-aqueous electrolyte, various organic solvents can be used as the non-aqueous solvent. For example, aprotic polar solvents are preferred. Specific examples thereof include cyclic carbonates such as ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, trifluoromethylethylene carbonate, fluoroethylene carbonate, and 4,5-difluoroethylene carbonate; lactones such as γ-butyrolactone and γ-valerolactone; cyclic sulfones such as sulfolane; cyclic ethers such as tetrahydrofuran and dioxane; ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, and methyl isopropyl carbonate. Examples of the fluorine-containing ethers include linear carbonates such as dipropyl carbonate, methyl butyl carbonate, dibutyl carbonate, ethyl propyl carbonate, and methyl trifluoroethyl carbonate; nitriles such as acetonitrile; linear ethers such as dimethyl ether; linear carboxylic acid esters such as methyl propionate; linear glycol ethers such as dimethoxyethane; and fluorine-containing ethers such as 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3,3-pentafluoropropyl ether, and ethoxy-2,2,2-trifluoroethoxy-ethane. These may be used alone or in combination of two or more.

[0050] As the non-aqueous solvent, from the viewpoint of ion conductivity, it is more preferable to use a carbonate-based solvent such as a cyclic carbonate or a chain carbonate. As the carbonate-based solvent, it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. As the cyclic carbonate, among the above, ethylene carbonate, propylene carbonate, and fluoroethylene carbonate are preferable. As the chain carbonate, among the above, ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate are preferable. When using a carbonate-based solvent, another non-aqueous solvent such as a nitrile-based compound or a sulfone-based solvent can be further added as necessary from the viewpoint of improving the battery physical properties.

[0051] The non-aqueous solvent preferably contains a chain carbonate, a saturated cyclic carbonate, and an unsaturated cyclic carbonate. It is particularly preferable to contain these three types of carbonate. The non-aqueous solvent preferably contains 30 to 80% by weight, 10 to 50% by weight, and 0.01 to 5% by weight of the chain carbonate, the saturated cyclic carbonate, and the unsaturated cyclic carbonate in the non-aqueous electrolyte, respectively, and more preferably contains 50 to 70% by weight, 20 to 30% by weight, and 0.1 to 2% by weight, respectively.

[0052] If the amount of the chain carbonate ester is less than 30% by weight, the viscosity of the electrolyte increases and solidifies at low temperatures, making it impossible to obtain sufficient characteristics, whereas if the amount is more than 80% by weight, the dissociation degree / solubility of the lithium salt decreases and the ionic conductivity of the electrolyte decreases. If the amount of the saturated cyclic carbonate ester is less than 10% by weight, the dissociation degree / solubility of the lithium salt decreases and the ionic conductivity of the electrolyte decreases, whereas if the amount is more than 50% by weight, the viscosity of the electrolyte increases and solidifies at low temperatures, making it impossible to obtain sufficient characteristics.

[0053] Furthermore, if the unsaturated cyclic carbonate is less than 0.01% by weight, a good coating is not formed on the surface of the negative electrode, resulting in a decrease in cycle characteristics. Conversely, if it is more than 5% by weight, the electrolyte becomes prone to gas generation during high-temperature storage, leading to an increase in the pressure inside the battery and other undesirable conditions for practical use.

[0054] Examples of the chain carbonate ester include chain carbonates having 3 to 9 carbon atoms. Specific examples include dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, di-n-propyl carbonate, diisopropyl carbonate, n-propyl isopropyl carbonate, di-n-butyl carbonate, di-t-butyl carbonate, n-butyl isobutyl carbonate, n-butyl-t-butyl carbonate, isobutyl-t-butyl carbonate, ethyl methyl carbonate, methyl-n-propyl carbonate, n-butyl methyl carbonate, Examples of the carbonate ester include isobutyl methyl carbonate, t-butyl methyl carbonate, ethyl-n-propyl carbonate, n-butyl ethyl carbonate, isobutyl ethyl carbonate, t-butyl ethyl carbonate, n-butyl-n-propyl carbonate, isobutyl-n-propyl carbonate, t-butyl-n-propyl carbonate, n-butyl isopropyl carbonate, isobutyl isopropyl carbonate, and t-butyl isopropyl carbonate. Among these, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate are preferred, but are not particularly limited. In addition, two or more of these chain carbonate esters may be mixed.

[0055] Examples of the saturated cyclic carbonate include ethylene carbonate, propylene carbonate, butylene carbonate, and fluoroethylene carbonate. Among these, ethylene carbonate, propylene carbonate, and fluoroethylene carbonate are more preferable, and the use of propylene carbonate can provide a stable nonaqueous electrolyte in a wide temperature range. Two or more of these saturated cyclic carbonates may be mixed.

[0056] Moreover, examples of the unsaturated cyclic carbonate ester include vinylene carbonate derivatives represented by the following general formula (I). [ka] In the above general formula (I), R1 and R2 are each independently a hydrogen atom, a halogen atom, or an alkyl group having a carbon number of 1 to 12 and optionally containing a halogen atom. Of these, it is preferable that R1 and R2 are hydrogen (vinylene carbonate).

[0057] Specific examples of the vinylene carbonate derivative include the following compounds: vinylene carbonate, fluorovinylene carbonate, methylvinylene carbonate, fluoromethylvinylene carbonate, ethylvinylene carbonate, propylvinylene carbonate, butylvinylene carbonate, dimethylvinylene carbonate, diethylvinylene carbonate, dipropylvinylene carbonate, etc., but are not limited thereto. Among them, vinylene carbonate is effective and advantageous in terms of cost. The vinylene carbonate derivatives are at least one type, and may be used alone or in combination. Another example of the unsaturated cyclic carbonate is an alkenyl ethylene carbonate represented by the following general formula (II).

[0058] [ka]

[0059] In the above formula (II), R3 to R6 are each independently a hydrogen atom, a halogen atom, a hydrocarbon group having 1 to 12 carbon atoms which may contain a halogen atom, or an alkenyl group having 2 to 12 carbon atoms, at least one of which is an alkenyl group having 2 to 12 carbon atoms. In particular, when one of R3 to R6 is a vinyl group and the rest are hydrogen, specific examples of the alkenyl ethylene carbonate include compounds such as 4-vinyl ethylene carbonate, 4-vinyl-4-methyl ethylene carbonate, 4-vinyl-4-ethyl ethylene carbonate, and 4-vinyl-4-n-propyl ethylene carbonate.

[0060] The non-aqueous solvent may contain various other solvents in addition to the above components. Examples of these various other solvents include cyclic carboxylates, chain esters having 3 to 9 carbon atoms, and chain ethers having 3 to 6 carbon atoms. These various other solvents are preferably contained in the non-aqueous electrolyte in an amount of 0.2 to 10% by weight, and particularly preferably 0.5 to 5% by weight.

[0061] Examples of cyclic carboxylates (lactone compounds having 3 to 9 carbon atoms) include γ-butyrolactone, γ-valerolactone, γ-caprolactone, ε-caprolactone, etc. Among these, γ-butyrolactone and γ-valerolactone are more preferred. In addition, two or more of these cyclic carboxylates may be mixed.

[0062] Examples of the chain ester having 3 to 9 carbon atoms include methyl acetate, ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, n-propyl propionate, isopropyl propionate, n-butyl propionate, isobutyl propionate, and t-butyl propionate. Of these, ethyl acetate, methyl propionate, and ethyl propionate are preferred.

[0063] Examples of chain ethers having 3 to 6 carbon atoms include dimethoxymethane, dimethoxyethane, diethoxymethane, diethoxyethane, ethoxymethoxymethane, ethoxymethoxyethane, etc. Among these, dimethoxyethane and diethoxyethane are more preferable.

[0064] Additionally, benzonitrile, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, dioxolane, 4-methyldioxolane, N,N-dimethylformamide, dimethylacetamide, dimethylsulfoxide, dioxane, sulfolane, dichloroethane, chlorobenzene, nitrobenzene, and the like can be used.

[0065] <Lithium salt> The non-aqueous electrolyte may contain a conventionally known lithium salt dissolved therein together with the electrolyte of the present invention. Specific examples of such lithium salts are as follows: (A) Inorganic lithium salt: Inorganic fluoride salts such as LiPF6, LiAsF6, LiBF4, etc., perhalogen salts such as LiClO4, LiBrO4, LiIO4, etc.

[0066] (B) Organic lithium salt: Organic sulfonates such as LiCF3SO3; perfluoroalkylsulfonate imide salts such as LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(CF3SO2)(C4F9SO2); perfluoroalkylsulfonate methide salts such as LiC(CF3SO2)3; LiPF(CF3)5, LiPF2(CF3)4, LiPF3(CF3)3, LiPF2(C2F5)4, LiPF3(C2F5)3, LiPF(n-C3F7)5, LiPF2(n-C3F7)4, LiPF3(n-C3F7)3, LiPF(iso-C3F7)5, LiPF2(iso-C3F7)4, LiPF3(iso-C3F73, LiB Examples of such fluorine-containing organic lithium salts include inorganic fluoride salts fluorophosphates in which some of the fluorine has been replaced with a perfluoroalkyl group, such as (CF3)4, LiBF(CF3)3, LiBF2(CF3)2, LiBF3(CF3), LiB(C2F5)4, LiBF(C2F5)3, LiBF2(C2F5)2, LiBF3(C2F5), LiB(n-C3F7)4, LiBF(n-C3F7)3, LiBF2(n-C3F7)2, LiBF3(n-C3F7), LiB(iso-C3F7)4, LiBF(iso-C3F7)3, LiBF2(iso-C3F7)2, and LiBF3(iso-C3F7).

[0067] Among the above, LiPF6, LiBF4, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(CF3SO2)(C2F5SO2) or LiN(CF3SO2)(C4F9SO2) are more preferred. Two or more of these lithium salts may be mixed.

[0068] The content of the electrolyte of the present invention in the nonaqueous electrolyte is preferably 0.01 to 10 mol / L, more preferably 0.01 to 3.0 mol / L. If the concentration is too low, the ionic conductivity of the nonaqueous electrolyte is insufficient due to an absolute lack of concentration, whereas if the concentration is too high, the ionic conductivity decreases due to an increase in viscosity, and precipitation at low temperatures is likely to occur, which is undesirable as it reduces the performance of the nonaqueous electrolyte battery.

[0069] In addition, when the non-electrolyte contains the above-mentioned known lithium compound, the lithium salt is preferably present in the non-aqueous electrolyte at 0.5 to 3 mol / L, particularly preferably 0.7 to 2 mol / L. If the concentration is too low, the ion conductivity of the non-aqueous electrolyte is insufficient due to an absolute lack of concentration, whereas if the concentration is too high, the ion conductivity decreases due to an increase in viscosity, and precipitation at low temperatures is likely to occur, which is undesirable as it reduces the performance of the non-aqueous electrolyte battery.

[0070] <Other additives> In order to improve the life performance and resistance performance of the power storage device, the nonaqueous electrolyte may contain other additives in addition to the lithium salt and lithium boron compound. As such other additives, for example, one or more selected from the group consisting of sulfur-containing compounds, cyclic acid anhydrides, carboxylic acid compounds, and boron-containing compounds can be used.

[0071] Examples of the sulfur-containing compound include 1,3-propane sultone (PS), propene sultone, ethylene sulfite, hexahydrobenzo[1,3,2]dioxathiolane-2-oxide (also referred to as 1,2-cyclohexanediol cyclic sulfite), 5-vinyl-hexahydro-1,3,2-benzodioxathiol-2-oxide, 1,4-butanediol dimethanesulfonate, 1,3-butanediol dimethanesulfonate, methylenemethane disulfonic acid, ethylenemethane disulfonic acid, N,N-dimethylmethanesulfonamide, N,N-diethylmethanesulfonamide, divinyl sulfone, and 1,2-bis(vinylsulfonyl)methane.

[0072] Examples of the cyclic acid anhydrides include glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, succinic anhydride, diglycolic anhydride, cyclohexanedicarboxylic anhydride, cyclopentanetetracarboxylic dianhydride, 4-cyclohexene-1,2-dicarboxylic anhydride, 3,4,5,6-tetrahydrophthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, phenylsuccinic anhydride, 2-phenylglutaric anhydride, phthalic anhydride, pyromellitic anhydride, fluorosuccinic anhydride, and tetrafluorosuccinic anhydride. carboxylic acid anhydrides such as 1,2-ethanedisulfonic acid anhydride, 1,3-propanedisulfonic acid anhydride, 1,4-butanedisulfonic acid anhydride, 1,2-benzenedisulfonic acid anhydride, tetrafluoro-1,2-ethanedisulfonic acid anhydride, hexafluoro-1,3-propanedisulfonic acid anhydride, octafluoro-1,4-butanedisulfonic acid anhydride, 3-fluoro-1,2-benzenedisulfonic acid anhydride, 4-fluoro-1,2-benzenedisulfonic acid anhydride, and 3,4,5,6-tetrafluoro-1,2-benzenedisulfonic acid anhydride.

[0073] Examples of the carboxylic acid compound include lithium oxalate, lithium malonate, lithium difluoromalonate, lithium succinate, lithium tetrafluorosuccinate, lithium adipate, lithium glutarate, lithium acetonedicarboxylate, lithium 2-oxobutyrate, lithium oxalacetate, lithium 2-oxoglutarate, lithium acetoacetate, 3-oxocyclobutanecarboxylic acid, 3-oxocyclopentanecarboxylic acid, lithium 2-oxovalerate, lithium pyruvate, lithium glyoxylate, and lithium 3, Examples of such lithium salts include lithium 3-dimethyl-2-oxobutyrate, lithium 2-hydroxypropionate, lithium 2-methyllactate, lithium tartrate, lithium cyanoacetate, lithium 2-mercaptopropionate, lithium methylenebis(thioglycolic acid)thiodisuccinate, lithium 3-(methylthio)propionate, lithium 3,3'-thiodipropionate, lithium dithiodiglycolate, lithium 2,2'-thiodiglycolate, lithium thiazolidine-2,4-dicarboxylate, and lithium acetylthioacetate.

[0074] Examples of the boron-containing compounds include LiBF2(C2O4), LiB(C2O4)2, LiBF2(CO2CH2CO2), LiB(CO2CH2CO2)2, LiB(CO2CF2CO2)2, LiBF2(CO2CF2CO2), LiBF3(CO2CH3), LiBF3(CO2CF3), LiBF2(CO2CH3)2, LiBF2(CO2CF3)2, LiBF(CO2CH3)3, LiBF(CO2CF3)3, LiB(CO2CH3)4, LiB(CO2CF3)4, Li2B2O7, Li2B2O4, etc. The above-mentioned other additives may be used alone or in combination of two or more. When the non-aqueous electrolyte contains an additive, the content of the additive in the non-aqueous electrolyte is preferably 0.01 to 5 mass %, and more preferably 0.1 to 2 mass %.

[0075] <Electricity storage device> As described above, the electrolyte of the present invention can be used in both non-aqueous electrolyte storage devices and all-solid-state storage devices. Examples of storage devices include various devices such as lithium (ion) secondary batteries, electric double-layer capacitors, and hybrid batteries in which one of the positive and negative electrodes is a battery and the other electrode is a double layer. In these storage devices, the electrolyte of the present invention can be used in any of the known methods and methods. A non-aqueous electrolyte lithium ion secondary battery, which is a typical example, will be described below.

[0076] As the negative electrode active material constituting the negative electrode in a lithium ion secondary battery, any of the following can be used: a carbon material capable of being doped / dedoped with lithium ions, metallic lithium, a lithium-containing alloy, or silicon, silicon alloy, tin, tin alloy capable of being alloyed with lithium, a tin oxide or silicon oxide capable of being doped / dedoped with lithium ions, a transition metal oxide capable of being doped / dedoped with lithium ions, a transition metal nitrogen compound capable of being doped / dedoped with lithium ions, or a mixture of these.

[0077] The negative electrode generally has a structure in which a negative electrode active material is formed on a current collector such as copper foil, expanded metal, etc. In order to improve the adhesion of the negative electrode active material to the current collector, for example, a polyvinylidene fluoride binder and a latex binder may be contained, and carbon black, amorphous whisker carbon, etc. may be added as a conductive assistant.

[0078] Examples of carbon materials constituting the negative electrode active material include pyrolytic carbons, cokes (pitch coke, needle coke, petroleum coke, etc.), graphites, fired organic polymer compounds (phenolic resins, furan resins, etc. fired at an appropriate temperature to carbonize), carbon fibers, activated carbon, etc. The carbon materials may be graphitized. As the carbon materials, carbon materials having a (002) plane interplanar spacing (d002) of 0.340 nm or less as measured by X-ray diffraction method and a true density of 1.70 g / cm are particularly preferred. 3 The above-mentioned graphite or a highly crystalline carbon material having similar properties is desirable. The use of such a carbon material can increase the energy density of a non-aqueous electrolyte battery.

[0079] Further, the carbon material may contain boron, be coated with a metal such as gold, platinum, silver, copper, Sn, or Si, or be coated with amorphous carbon, etc. These carbon materials may be used alone or in combination of two or more.

[0080] In addition, when silicon, silicon alloys, tin, tin alloys, which can be alloyed with lithium, tin oxide, silicon oxide, which can be doped and dedoped with lithium ions, and transition metal oxides, which can be doped and dedoped with lithium ions, are used, all of them have a higher theoretical capacity per weight than the above-mentioned carbonaceous materials, and are suitable materials.

[0081] On the other hand, the positive electrode active material constituting the positive electrode can be formed from various materials capable of charging and discharging. Examples include lithium-containing transition metal oxides, lithium-containing transition metal composite oxides using one or more transition metals, transition metal oxides, transition metal sulfides, metal oxides, olivine-type metal lithium salts, etc. Examples include composite oxides of lithium and one or more transition metals (lithium transition metal composite oxides) represented by LixMO2 (where M is one or more transition metals, x varies depending on the charge / discharge state of the battery and is usually 0.05≦x≦1.20), such as LiCoO2, LiNiO2, LiMn2O4, and LiMnO2.

[0082] Furthermore, composite oxides in which some of the transition metal atoms that are the main components of the lithium transition metal composite oxides are substituted with other metals such as Al, Ti, V, Cr, Mn, Fe, Co, Li, Ni, Cu, Zn, Mg, Ga, Zr, Si, Yb, chalcogenides of transition elements such as FeS2, TiS2, V205, MoO3, MoS2, or polymers such as polyacetylene and polypyrrole can be used. Of these, lithium transition metal composite oxides that can be doped and dedoped with Li and metal composite oxide materials in which some transition metal atoms are substituted can be used.

[0083] In addition, a material having a different composition from the material constituting the main positive electrode active material may be attached to the surface of the positive electrode active material. Examples of the surface-attaching material include oxides such as aluminum oxide, silicon oxide, titanium oxide, zirconium oxide, magnesium oxide, calcium oxide, boron oxide, antimony oxide, and bismuth oxide; sulfates such as lithium sulfate, sodium sulfate, potassium sulfate, magnesium sulfate, calcium sulfate, and aluminum sulfate; and carbonates such as lithium carbonate, calcium carbonate, and magnesium carbonate.

[0084] The positive electrode generally has a configuration in which a positive electrode active material is formed on a current collector such as an aluminum, titanium, or stainless steel foil, or an expanded metal, etc. In order to improve the adhesion of the positive electrode active material to the current collector, for example, a polyvinylidene fluoride binder and a latex binder may be contained, and in order to improve the electronic conductivity in the positive electrode, carbon black, amorphous whiskers, graphite, etc. may be contained.

[0085] The separator is preferably a film that electrically insulates the positive electrode and the negative electrode and is permeable to lithium ions, and a porous film such as a microporous polymer film is used. As the microporous polymer film, a porous polyolefin film is particularly preferable, and more specifically, a porous polyethylene film, a porous polypropylene film, or a multilayer film of a porous polyethylene film and a polypropylene film is preferable. Furthermore, a polymer electrolyte can be used as the separator. As the polymer electrolyte, for example, a polymer substance in which a lithium salt is dissolved, or a polymer substance swollen with an electrolytic solution can be used, but is not limited thereto.

[0086] The nonaqueous electrolyte may be used for the purpose of obtaining a polymer electrolyte by swelling a polymer substance with the nonaqueous electrolyte, or the nonaqueous electrolyte may be impregnated into a separator in which a porous polyolefin film and a polymer electrolyte are combined. The shape of a lithium ion secondary battery using the nonaqueous electrolyte of the present invention is not particularly limited, and it can be in various shapes such as a cylindrical type, a square type, a laminate type, a coin type, and a button type. EXAMPLES

[0087] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples and can be modified within the scope of the present invention. <Battery Construction> A flat wound electrode group in which the positive and negative electrodes were wound with a 23 μm thick separator (F23DHA, manufactured by Toray Battery Separator Film Co., Ltd.) between them was used to fabricate a battery cell having a rectangular parallelepiped shape of 30 mm in length, 30 mm in width, and 2.0 mm in thickness. The electrode group was then housed in a case to fabricate a battery cell. Positive electrode: 5% by mass of polyvinylidene fluoride as a binder, 4% by mass of acetylene black as a conductive agent, and positive electrode active material LiNi, which is a composite oxide powder of lithium, nickel, manganese, and cobalt. 0.6 Mn 0.2 Co 0.2 A positive electrode composite material was prepared by mixing 91% by mass of O2 and N-methylpyrrolidone to prepare a paste. This was then applied to both sides of an 18 μm-thick aluminum foil current collector. After the solvent was dried and removed, the current collector was rolled using a roll press to produce a positive electrode.

[0088] Negative electrode: 95.8% by mass of artificial graphitizable carbon powder, 2.0% by mass of styrene butadiene rubber (SBR) as a binder, and 2.2% by mass of carboxymethyl cellulose in water were mixed and used as a dispersion medium to prepare a slurry. This slurry was applied to both sides of a 12 μm-thick copper foil, the solvent was dried off, and then the foil was rolled using a roll press to produce a negative electrode.

[0089] Using the battery cell produced above, a lithium ion secondary battery was produced according to the following steps a to c. a. 0.55 g of each electrolyte was weighed out and poured into the inlet of the battery cell. After the pressure was reduced, the inlet was sealed. b. The sealed battery cell was kept in an atmosphere of 25°C and charged to 4.2V at 8mA, and then discharged to 3.0V at 8mA. c. The internal gas of the battery cell discharged to 3.0 V was removed under reduced pressure to prepare a battery.

[0090] <Battery evaluation> The charge / discharge characteristics of the battery prepared above were measured as follows. a.Rate of resistance change Before the high-temperature cycle test, the batteries were charged to a SOC (State of Charge) of 50% at 25° C., and then discharged for 10 seconds at 0.2 C, 0.5 C, 1.0 C, and 2.0 C in each environment to determine the initial DC resistance. The battery was charged to 4.2 V at 1 C rate in a 45° C. atmosphere, and then discharged to 3.0 V at 1 C rate in the same atmosphere, and this cycle was repeated until 200 cycles were reached, after which the DC resistance after the cycles was calculated under the same conditions as before the high-temperature cycle test. The resistance change rate (%) was calculated from the initial DC resistance and the DC resistance after the cycles using the following formula (1). Resistance change rate = (resistance after cycling / initial resistance) x 100 (1)

[0091] b.Capacity retention rate After charging to 4.2 V at 1 C rate in a 45°C atmosphere, the battery was discharged to 3.0 V at 1 C rate in the same atmosphere, and the discharge capacity value was taken as the initial capacity value. The same conditions were then repeated until 200 cycles were reached. The capacity retention rate (%) was calculated from the initial capacity value and the capacity value after cycling using the following formula (2). Capacity retention rate = (capacity after cycling / initial capacity) x 100 (2) <Example A Series>

[0092] <Production Example 1> Under an argon atmosphere, 100 ml of methanol was placed in a 500 ml Erlenmeyer flask, 30 g of lithium oxide was added, and the mixture was cooled to 10° C. with stirring. Next, the mixture was kept at 10° C. and 290 g of boron trifluoride methanol complex was added over 5 hours with stirring, and the reaction solution was kept at 50° C. and stirred for 3 hours. The reaction solution was then concentrated to remove the methanol, and a crude lithium oxide / 2BF3 complex was obtained. The resulting crude lithium oxide / 2BF3 complex was washed three times with 50 ml of dibutyl ether each to remove excess boron trifluoride methanol complex. The resulting solid was then dried under reduced pressure at 110°C for 10 hours, yielding 157 g of lithium oxide and 2BF3 complex O-(BF3Li)2. The solid obtained was analyzed by ICP, and the boron content was 99.5 per 100 lithium.

[0093] <Production Example 2> The same procedure as in Production Example 1 was carried out except that 132 g of boron trifluoride methanol complex was used instead of 290 g of boron trifluoride methanol complex, to obtain 91 g of lithium oxide / BF3 complex (O-(BF3Li)(Li)). The solid was analyzed by ICP and found to contain 48 parts boron per 100 parts lithium.

[0094] <Production Example 3> Under an argon atmosphere, 100 ml of methanol was placed in a 500 ml Erlenmeyer flask, and 23 g of lithium sulfide was added thereto, and the mixture was then cooled to 10° C. with stirring. Next, the above mixture was kept at 10° C., and 155 g of boron trifluoride diethyl ether complex was added over 5 hours, and then the reaction mixture was kept at 50° C. and stirred for 3 hours. Next, diethyl ether was removed from the reaction solution to obtain a crude lithium sulfide / 2BF3 complex. The obtained crude lithium sulfide / 2BF3 complex was washed three times with 50 ml of dibutyl ether. The obtained solid was then dried under reduced pressure for 10 hours at 110°C to obtain 87 g of lithium sulfide / 2BF3 complex (S-(BF3Li)2). The obtained solid was analyzed using ICP, and the boron content was 99.8 per 100 lithium.

[0095] <Production Example 4> Under an argon atmosphere, the same procedure as in Production Example 3 was carried out except that 76 g of boron trifluoride diethyl ether complex was used instead of 155 g of boron trifluoride diethyl ether complex, thereby obtaining 53 g of lithium sulfide / BF3 complex (S-(BF3Li)(Li)). The solid was analyzed by ICP and found to contain 51 parts boron per 100 parts lithium.

[0096] <Production Example 5> In a 300 ml beaker, 50 ml of methanol and 44 g of boron trifluoride methanol complex were placed to prepare a mixed solution. Next, this mixture was kept at 10° C. under an argon atmosphere, and 3.4 g of lithium nitride was added thereto over a period of 5 hours with stirring. The reaction solution was then concentrated to remove the methanol, and a crude lithium nitride / 3BF3 complex was obtained. The resulting crude lithium nitride / 3BF3 complex was washed three times with 20 ml of dibutyl ether each. The resulting solid was then dried under reduced pressure at 110°C for 10 hours, yielding 18 g of lithium nitride / 3BF3 complex (N-(BF3Li)3). The resulting solid was analyzed using ICP, and the boron content was 98.5 per 100 lithium.

[0097] <Production Example 6> The same procedure as in Production Example 5 was carried out except that 29.5 g of boron trifluoride methanol complex was used instead of 44 g of boron trifluoride methanol complex, thereby obtaining 14.5 g of lithium nitride / 2BF3 complex (N-(BF3Li)2(Li)). The solid was analyzed by ICP and found to contain 68 elements of boron per 100 parts of lithium.

[0098] <Production Example 7> A mixture was prepared by adding 50 ml of methanol and 44 g of boron trifluoride methanol complex to a 300 ml beaker. Next, this mixture was kept at 10°C under an argon atmosphere, and 5.2 g of trilithium phosphide was added over 5 hours while stirring. The reaction solution was then concentrated to remove methanol, and a crude lithium phosphide / 3BF3 complex was obtained. The resulting crude lithium phosphide / 3BF3 complex was washed three times with 20 ml of dibutyl ether each. The resulting solid was then dried under reduced pressure for 10 hours at 110°C, yielding 19 g of lithium phosphide / 3BF3 complex (P-(BF3Li)3). The resulting solid was analyzed using ICP, and the boron content was 90 per 100 lithium.

[0099] <Production Example 9> Under an argon atmosphere, 50 ml of methanol was placed in a 300 ml Erlenmeyer flask, and 27 g of lithium metasilicate was added thereto, and the mixture was then cooled to 10° C. with stirring. Next, the above mixture was kept at 10° C., and 86 g of boron trifluoride methanol complex was added over 5 hours, after which the reaction mixture was kept at 50° C. and stirred for 3 hours. Next, methanol was removed from the reaction solution to obtain a crude lithium metasilicate / 2BF3 complex. The obtained crude lithium metasilicate / 2BF3 complex was washed three times with 50 ml of dibutyl ether. The obtained solid was then dried under reduced pressure for 10 hours at 110°C to obtain 62 g of lithium metasilicate / 2BF3 complex (SiO3-(BF3Li)2). The obtained solid was analyzed using ICP, and the boron content was 99.5 per 100 lithium.

[0100] <Production Example 10> The same procedure as in Production Example 9 was carried out except that 43 g of boron trifluoride methanol complex was used instead of 86 g of boron trifluoride methanol complex, to obtain 14.5 g of lithium metasilicate / 2BF3 complex ((SiO3-(BF3Li)(Li)). The solid was analyzed by ICP and found to contain 49 elements of boron per 100 parts of lithium.

[0101] <Examples 1 to 4> When the electrolyte, O-(BF3Li)2 or S-(BF3Li)2, was added to a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and vinylene carbonate (VC) (volume ratio 30:68:2), it dissolved well, and thus each of the electrolyte solutions used in Examples 1 to 4 shown in Table 1 was prepared. Using each of the electrolyte solutions prepared above, the batteries of Examples 1 to 4 were produced according to the battery production procedure described above, and then the resistance change rate and capacity retention rate were determined. The results are shown in Table 1.

[0102] [Table 1] As shown in Table 1, the batteries of Examples 1 to 4 exhibited the effect of maintaining a high cycle capacity retention rate and suppressing the rate of resistance change to a low level.

[0103] <Examples 5 to 8, Comparative Example 1> A reference electrolyte 1 was prepared by dissolving LiPF6 as a lithium salt in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 30:70) to a concentration of 1 mol / L. Next, O-(BF3Li)2 was added to this reference electrolyte 1 to prepare each electrolyte in the amount shown in Table 2. The amount (%) added in Table 2 is the mass % of the electrolyte added relative to the total mass (100 mass %) of reference electrolyte 1 and the electrolyte. Using each of the electrolyte solutions prepared above, laminate batteries of Examples 5 to 8 were produced according to the battery production procedure described above, and the resistance change rate and capacity retention rate were then determined. The results are shown in Table 2.

[0104] [Table 2]

[0105] As shown in Table 2, the addition of a lithium compound and a boron trifluoride complex significantly reduces the resistance change rate during high-temperature cycling and also improves the capacity retention rate after cycling.

[0106] <Examples 9 to 17, Comparative Example 2> LiPF6 was added as a lithium salt to a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) (volume ratio 30:67:3) to a concentration of 1 mol / L, and then dissolved to prepare reference electrolyte 2. Next, each electrolyte shown in Table 3 was added to this reference electrolyte solution 2 in the amount shown in Table 3 to prepare each electrolyte solution. The amount (%) added in Table 3 is the mass % of the electrolyte added relative to the total mass (100 mass %) of reference electrolyte solution 1 and the electrolyte.

[0107] After the laminate batteries of electrolytic solutions 9 to 17 and Comparative Example 2 shown in Table 3 were produced, the resistance change rate and capacity retention rate were determined.

[0108] [Table 3]

[0109] As shown in Table 3, the resistance change rate during high-temperature cycles was significantly reduced by adding the lithium-containing complex compound, and in particular, in Examples 7, 8, 12, and 13, the degree of improvement was large. In addition, the capacity retention rate after cycling can be improved. Among them, compound A containing O, S, and Si elements can significantly improve the capacity retention rate.

[0110] <Examples 18 to 17> A reference electrolyte 3 was prepared by adding LiPF6 as a lithium salt to a mixed solvent (volume ratio 30:70) of ethylene carbonate (EC) and diethyl carbonate (DEC) to a concentration of 1 mol / L and then dissolving it. Next, S-(BF3Li)2 was added to the above-mentioned reference electrolyte 3 so that the amount added was 0.3 mass%, and further, additives shown in Table 4 were added so that the amount added (%) was shown in Table 4, to prepare each of the electrolytes of Examples 18 to 21. Note that no S-(BF3Li)2 was added to the electrolyte of Comparative Example 3. The amount added is in mass% relative to the total mass (100 mass%) of the reference electrolyte 3, S-(BF3Li)2, and additives.

[0111] Using the electrolytes 14 to 17 and the reference electrolyte 3 shown in Table 4, laminate batteries of Examples 14 to 17 and Comparative Example 3 were prepared according to the above-mentioned battery preparation procedure, and the resistance change rate and capacity retention rate were then determined. The results are shown in Table 4.

[0112] [Table 4]

[0113] As shown in Table 4, the addition of lithium compound A and boron trifluoride complex has the effect of significantly improving the capacity retention rate during high-temperature cycles and significantly reducing the rate of resistance change after cycles.

[0114] <Example B Series> <Production Example 1> In a 200 ml beaker, 50 ml of ion-exchanged water was placed, and 6.2 g of boric acid was added, and the mixture was heated to 60° C. with stirring. Next, the mixture was kept at 60° C., and 72 g of 10% by mass lithium hydroxide was added with stirring, and further stirred for 12 hours while keeping the temperature at 60° C. The reaction solution was then concentrated to dryness and dried under reduced pressure at 200° C. for 12 hours, after which it was pulverized to obtain a white powder of trilithium borate. Then, under an argon atmosphere, the above-mentioned white powder of trilithium borate and 30 ml of diethyl ether were placed in a 100 ml Erlenmeyer flask, and the mixed liquid was cooled to 10° C. with stirring. Next, the above-mentioned mixed liquid was kept at 20° C. and 45 g of boron trifluoride diethyl ether complex was added over 3 hours with stirring, and then the reaction liquid was kept at 50° C. and stirred for 3 hours. Next, the diethyl ether was removed to obtain a crude B-(OBF3Li)3 complex. The crude was washed three times with 10 ml of dibutyl ether to remove excess boron trifluoride diethyl ether complex. The solid was then dried under reduced pressure at 110°C for 10 hours to obtain B-(OBF3Li)3, which is a lithium borate and 3BF3 complex. The solid obtained was analyzed by ICP, and the ratio of lithium atoms to boron atoms was found to be 3:4.

[0115] <Production Example 2> LiBO-(OBF3Li)2, which is a lithium borate and 2BF3 complex, was obtained by carrying out the same procedure as in Production Example 1, except that 29 g of boron trifluoride diethyl ether complex was used instead of 45 g of boron trifluoride diethyl ether complex. The solid obtained was analyzed by ICP, and the ratio of lithium atoms to boron atoms was found to be 1:1.

[0116] <Production Example 3> A white powder of dilithium borate was obtained by carrying out the same procedure as in Production Example 1, except that 50 g of 10 mass % lithium hydroxide was used instead of 72 g of 10 mass % lithium hydroxide. The same procedure as in Production Example 1 was carried out except that 29 g of boron trifluoride diethyl ether complex was used instead of 45 g of boron trifluoride diethyl ether complex, thereby obtaining dilithium borate and 2BF3 complex, B2O-(OBF3Li)4. The solid obtained was analyzed by ICP, and the ratio of lithium atoms to boron atoms was found to be 2:3.

[0117] <Production Example 4> In a 300 ml beaker, 100 ml of ion-exchanged water was placed, 31 g of boric acid was added, and the mixture was heated to 60° C. while stirring. Next, the mixture was kept at 60° C., and 30 g of 10% by mass lithium hydroxide was added while stirring, and the mixture was further stirred for 12 hours while keeping the temperature at 60° C. Next, the reaction liquid was concentrated to dryness, dried under reduced pressure in an atmosphere of 200° C. for 12 hours, and then pulverized to obtain a white powder. Then, under an argon atmosphere, the obtained white powder and 50 ml of diethyl ether were placed in a 300 ml Erlenmeyer flask, and the mixed liquid was cooled to 10° C. with stirring. Next, the mixed liquid was kept at 20° C. and 16 g of boron trifluoride diethyl ether complex was added over 3 hours with stirring, and then the reaction liquid was kept at 50° C. and stirred for 3 hours. Then, the diethyl ether was removed to obtain a crude B5O7-(OBF3Li) complex. The resulting crude complex was washed three times with 50 ml of dibutyl ether to remove excess boron trifluoride diethyl ether complex, and the resulting solid was dried under reduced pressure at 110°C for 10 hours to obtain the B5O7-(OBF3Li) complex. The solid obtained was analyzed by ICP, and the ratio of lithium atoms to boron atoms was found to be 1:6.

[0118] <Production Example 5> In a 200 ml beaker, 50 ml of ion-exchanged water was placed, and 6.2 g of boric acid was added. The mixture was kept at 25° C., and 22.8 g of trifluoroacetic acid was slowly added while stirring. The mixture was then stirred for 12 hours while maintaining the temperature at 60° C. The reaction liquid was then kept at 25° C. and 24 g of 10% by mass lithium hydroxide was added, followed by stirring for 12 hours while maintaining at 60° C. The reaction liquid was then concentrated to dryness, dried under reduced pressure in an atmosphere at 120° C. for 6 hours, and pulverized to obtain a white powder. Then, under an argon atmosphere, the obtained white powder and 50 ml of diethyl ether were placed in a 200 ml Erlenmeyer flask, and the mixed liquid was cooled to 10° C. with stirring. Next, the mixed liquid was kept at 20° C. and 16 g of boron trifluoride diethyl ether complex was added over 3 hours with stirring, and then the reaction liquid was kept at 50° C. and stirred for 3 hours.

[0119] Next, the diethyl ether was removed to obtain a crude B(OC(=O)CF3)2(OBF3Li) complex. The obtained crude was washed three times with 50 ml of dibutyl ether to remove excess boron trifluoride diethyl ether complex. The obtained solid was then dried under reduced pressure for 10 hours at 110°C to obtain the B(OC(=O)CF3)2(OBF3Li) complex. The solid obtained was analyzed by ICP, and the ratio of lithium atoms to boron atoms was found to be 1:2.

[0120] <Production Examples 6 to 8> The same procedures as in Production Example 1 were carried out except that 9 g of oxalic acid (Production Example 6), 10.4 g of malonic acid (Production Example 7), and 15 g of thiodiacetic acid (Production Example 8) were used instead of 22.8 g of trifluoroacetic acid, thereby obtaining a B(OOC-COO)(OBF3Li) complex (Production Example 6), a B(OOCCH2COO)(OBF3Li) complex (Production Example 7), and a B(OOCCH2SCH2COO)(OBF3Li) complex (Production Example 8). The solid obtained was analyzed by ICP, and the ratio of lithium atoms to boron atoms was found to be 1:2.

[0121] <Examples 1 to 6> Each electrolyte shown in Table 5 was added to a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC) and vinylene carbonate (VC) (volume ratio 30:30:38:2) in the amount shown in Table 5 to prepare each of the electrolytes used in Examples 1 to 4 shown in Table 5. The amount of electrolyte added in Table 5 is in moles / liter based on lithium. Using each of the electrolyte solutions prepared above, the batteries of Examples 1 to 6 were produced according to the battery production procedure described above, and the resistance change rate and capacity retention rate were then determined. The results are shown in Table 5.

[0122] [Table 5] As shown in Table 5, the batteries of Examples 1 to 6 exhibited the effect of maintaining a high cycle capacity retention rate and suppressing the rate of resistance change to a low level.

[0123] <Examples 7 to 19> Reference electrolyte 1 was prepared by dissolving LiPF6 as a lithium salt in a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 30:70) to a concentration of 1 mol / L in 99 g of solution, to which 1 g of vinylene carbonate was further added. Next, a lithium-containing boron complex compound shown in Table 6 was added to this reference electrolyte 1 in the amount shown in Table 6 to prepare each of the electrolytes used in Examples 7 to 20 and Comparative Example 1. The amount added (%) in Table 6 is the mass % relative to the total mass (100 mass %) of the reference electrolyte 1 and the compound in question.

[0124] Using each of the electrolyte solutions prepared above, the batteries of Examples 7 to 20 and Comparative Example 1 were produced according to the above battery production procedure, and then the resistance change rate and capacity retention rate were determined according to the above procedures for the resistance change rate and capacity retention rate. The results are shown in Table 6.

[0125] [Table 6]

[0126] As shown in Table 6, the addition of the lithium-containing boron complex compound significantly reduced the resistance change rate during high-temperature cycling and also improved the capacity retention rate after cycling.

[0127] <Examples 21 to 24> A reference electrolyte 2 was prepared by adding and dissolving LiPF6 as a lithium salt to a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 30:70) to a concentration of 1 mol / L. Next, B-(OBF3Li)3 was added to the above-mentioned reference electrolyte 2 so that the amount added was 0.5 mass %, and further, the additives shown in Table 7 were added so that the amount added was the % in Table 7, to prepare each of the electrolytes of Examples 20 to 23. Note that no B-(OBF3Li)3 was added to the electrolyte of Comparative Example 2. The amount added is the mass % relative to the total mass (100 mass %) of the reference electrolyte 2, B-(OBF3Li)3, and the additives.

[0128] Using the electrolytes 21 to 24 and reference electrolyte 2 shown in Table 7, the batteries of Examples 21 to 24 and Comparative Example 2 were fabricated according to the above-mentioned battery fabrication procedure, and the resistance change rate and capacity retention rate were then determined. The results are shown in Table 7.

[0129] [Table 7]

[0130] As shown in Table 7, the addition of the lithium-containing boron complex compound improved the capacity retention rate during high-temperature cycling and significantly reduced the rate of resistance change after cycling. [Industrial Applicability]

[0131] A nonaqueous electrolyte solution type or all-solid electrolyte type lithium secondary battery using the electrolyte for electricity storage devices of the present invention is widely used for electricity storage devices such as power sources for various consumer appliances such as mobile phones and laptop computers, power sources for industrial equipment, storage batteries, and power sources for automobiles.

Claims

1. An electricity storage device having a positive electrode, a negative electrode, and an electrolyte provided between the two electrodes, wherein the electrolyte contains a lithium-containing complex compound represented by the following formula (1), formula (2), formula (3), formula (4), or formula (5), and the negative electrode contains at least one negative electrode active material selected from the group consisting of a carbon material, metallic lithium, a lithium-containing alloy, silicon, a silicon alloy, tin, a tin alloy, tin oxide, silicon oxide, a transition metal oxide, and a transition metal nitrogen compound. <h2 style=";text-align:left;direction:ltr">((Li)<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> ((A)<h2 style=";text-align:left;direction:ltr"> n <h2 style=";text-align:left;direction:ltr"> ((UF<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> )<h2 style=";text-align:left;direction:ltr"> y <h2 style=";text-align:left;direction:ltr"> (1) (Li) m (Yes) n (O) q (UF) x ) y (2) (In the formula, A is O, S, P or N. U is a boron atom or a phosphorus atom. m and n each independently are 1 to 6. q is 1 to 12. x is 3 or 5. y is 1 to 6.) (Li) m (O) n (B) p (OTF q ) x (3) (In the formula, W is a boron atom or a phosphorus atom; m, p, and x each independently are 1 to 15; n is 0 to 15; and q is 3 or 5.) (Li) m (B) p (O) n (OR) y (OWF q ) x (4) (In the formula, W is a boron atom or a phosphorus atom; n is 0 to 15; p, m, x, and y are each independently 1 to 12; and q is 3 or 5. R is a hydrogen atom, an alkyl group, an alkenyl group, an aryl group, a carbonyl group, or a sulfonyl group, and these groups may have a fluorine atom, an oxygen atom, and other substituents.) (Li) m (O) n (B) p (OOC-(A) z -COO) y (OWF q ) x (5) (In the formula, W is a boron atom or a phosphorus atom; A is an alkylene group, an alkenylene group or an alkynylene group having 1 to 6 carbons, a phenylene group, or an alkylene group having an oxygen atom or a sulfur atom in the main chain; m, p, x, and y each independently are 1 to 20; n is 0 to 15; z is 0 or 1; and q is 3 or 5.)

2. 2. The electricity storage device according to claim 1, wherein the carbon material is selected from the group consisting of pyrolytic carbons, cokes, graphites, fired organic polymer compounds, carbon fibers, activated carbon, and mixtures thereof, and is a carbon material coated with gold, platinum, silver, copper, Sn, or Si, or is the gold, platinum, silver, copper, Sn, or Si coated with amorphous carbon.

3. 3. The electricity storage device according to claim 1, which is a lithium ion secondary battery.

Citation Information

Patent Citations

  • Non-aqueous electrolyte for lithium electrochemical batteries

    JP2005536832A

  • Electrolyte and lithium ion secondary battery

    JP2015092471A

  • Electrolytes and non-aqueous electrolytes for power storage devices

    JP7627973B2

  • Non-aqueous electrolyte and power storage device using same

    WO2013168821A1

  • Nonaqueous electrolyte solution for batteries, novel compound, polymer electrolyte, and lithium secondary battery

    WO2014175225A1